Global imbalances, monetary disorder, and shrinking policy space: Keynes's legacy for our troubled world - Anna M. Carabelli; Mario A. Cedrini (Intervention. European Journal of Economics and Economic Policies, 2010)
The paper aims at showing that revisiting Keynes's early writings on international economic relations and some less well-known episodes of his economic diplomacy, with special attention being paid to the methodological issues involved, may disclose useful insights in understanding the features of his desired new global order. We contrast the three main pillars of Keynes's vision as detected in this revisitation (coordinated multilateral responses to global imbalances, a rational international monetary regime, and enhanced policy space) with the major shortcomings of the current non-system, and show the continuing relevance not only of Keynes's specific proposals for global reform, but also, and most importantly, the legacy of his way of reasoning about international economic relations.
Keywords: B31; F02; B41; 330; John Maynard Keynes; international economic order; Bretton Woods II